ANALISIS PENERAPAN EMPLOYEE ENGAGEMENT DALAM UPAYA MENUNJANG KOMITMEN KERJA AIR TRAFFIC CONTROLLER (ATC) PADA PERUM LPPNPI BANDARA KERTAJATI - Totok Priyono; Sola Gratia Br Bukit; Eka Rofiyanti (JAMBIS : Jurnal Administrasi Bisnis, 2023)
This study aims to determine how employee engagement is implemented, obstacles in the application of employee engagement, and solutions in resolving obstacles in implementing employee engagement in an effort to support the work commitment of Air Traffic Controller (ATC) at Kertajati Airport. This is based on the problem in which the age of Kertajati Airport is still relatively young, many employees want to move, and employees do not have strong emotional loyalty and attachment to Kertajati Airport, so that their work commitment can be said to be low. This research was conducted at Kertajati Airport from May 2020 to September 2020. This research used a qualitative approach. Data collection was carried out by means of observation, in-depth interviews, and literature study. Interviews were conducted with 7 informants. The concept used is employee engagement. Based on the data obtained, it can be seen that Air Traffic Controller (ATC) employees have implemented Employee Engagement. Internal and external obstacles, such as: a) differences of opinion; b) uneven training; c) misunderstanding between colleagues; d) overlapping tasks; e) the distance from Kertajati International Airport which is far from the employee's house. Efforts are made to overcome obstacles: Have lots of discussions between employees so that there are no misunderstandings or differences of opinion, take the time to go to work and go home on time so that they can arrive at their destination in the expected time